Dietary Selenium Alleviated Mouse Liver Oxidative Stress and NAFLD Induced by Obesity by Regulating the KEAP1/NRF2 Pathway - Yi Wang; Bingbing Liu; Peixuan Wu; Yi Chu; Sisi Gui; Yazhen Zheng; Xiaodong Chen (Antioxidants, 2022)
Nonalcoholic fatty liver disease (NAFLD) occurs when excess fat is stored in the liver and it is strongly linked with metabolic syndrome and oxidative stress. Selenium (Se) is an essential micronutrient in animals, which has a variety of biological functions, including antioxidant and anti-inflammatory. However, the exact effect of dietary selenium on NAFLD and the underlying molecular mechanism are not yet clear. Herein, we fed a high-fat diet (HFD) to C57BL/6 mice to construct an in vivo NAFLD model, treated AML-12 cells with palmitic acid (PA) to construct an in vitro NAFLD model, and AML-12 cells were stimulated with H2O2 to induce hepatocyte oxidative stress and then treated with adequate selenium. We observed that adequate selenium significantly improved the hepatic injury and insulin resistance in HFD mice, and decreased the fat accumulation and the expression of lipogenic genes in PA-induced AML-12 cells. Meanwhile, selenium significantly inhibited the production of reactive oxygen species (ROS), inhibited apoptosis, and restored mitochondrial number and membrane potential in PA- induced AML-12 cells. In addition, selenium can promote selenoproteinP1 (SEPP1) synthesis to regulate the Kelch-like ECH-associated protein 1 (KEAP1)/NF-E2-related factor 2 (NRF2) pathway, so as to defend against hepatocyte oxidative stress. These findings suggest that dietary selenium supplementation can effectively resist hepatic injury and insulin resistance during NAFLD development, and regulate the KEAP1/NRF2 pathway to resist oxidative stress by promoting SEPP1 synthesis.